Legal rules for preventing and combating cyber crimes in Algerian legislation - BELLAROU, Kamel (Journal of Human Sciences, 2024)
This study seeks to shed light on the legal mechanisms to prevent and combat cyber-crimes Of Technological development Supernatural that The entire world has known it, especially the enormous information wealth and economic liberation in the context of globalization, the widespread spread of electronic networks and the emergence of modern means of technology and communication that have imposed themselves in all aspects of life. This development has been accompanied by the emergence of new types of innovative crime that differ in terms of their nature and their perpetrators. And the methods of committing them compared to traditional crimes,a resultano The widespread use of the World Wide Web, which allowed individuals to exchange and circulate information And follow digitization systems in all fields Without knowing any spatial or temporal limits, which resulted in compromising the interests of individuals, institutions, and basic interests protected by law. And we aim for This study sheds light on information crime to identify it and explain its legal framework, in addition to examining the legal mechanisms to combat information crime at the level. The shop and international.